2014 Oceans - St. John's 2014
DOI: 10.1109/oceans.2014.7003187
|View full text |Cite
|
Sign up to set email alerts
|

Development of an underwater electric field modem

Abstract: An overview of electromagnetic propagation in seawater is discussed with some applications found in the literature. An experiment involving vertical dipoles submerged in seawater was performed to measure the frequency response at different ranges. The experimental results indicate that this dipole configuration can be effectively modeled as two vertical dipoles in a homogenous medium. Lastly, we provide a brief description of the current state of development of our underwater electric field modem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
(12 reference statements)
1
4
0
Order By: Relevance
“…The results from simulation of antennas in sea water and simulations of antennas placed on seabed at several distances (d) are compared in Figure 7 . As it can be seen, sea water attenuation is dramatically increased as frequencies are higher, which is coherent with theoretical graphs in literature [ 8 ]. Moreover, there are clearly two distinguishable areas, A and B, separated by a black dashed line in the figure.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The results from simulation of antennas in sea water and simulations of antennas placed on seabed at several distances (d) are compared in Figure 7 . As it can be seen, sea water attenuation is dramatically increased as frequencies are higher, which is coherent with theoretical graphs in literature [ 8 ]. Moreover, there are clearly two distinguishable areas, A and B, separated by a black dashed line in the figure.…”
Section: Resultssupporting
confidence: 89%
“…Regarding antennas, loop antennas and different types of dipoles are usually tested by research groups, but no agreement has been found on which is the best choice. Dipoles with and without insulated sections are examined in [ 7 , 8 , 9 ], whilst others carry out experiments with loop antennas [ 7 ]. Nevertheless, magnetic loop antennas seem to have a certain acceptance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In shallow waters, the medium presents two alternative propagation mechanisms for EM waves: the water-to-air and water-to-seafloor interfaces, e.g., [7,8]. Since these interfaces present less conductivity than seawater, depending on the relative position of the transceivers and receivers with regards to the surface and seafloor, the communication range of the EM communication in shallow water is usually larger than over a homogeneous medium.…”
Section: Introductionmentioning
confidence: 99%
“…However, they overcome all the negative aspects that acoustic and optical systems suffer in shallow seawater. Many studies dealing with EM signal in seawater describe alternative propagation mechanisms [7] [5]. The shallow water environment presents two interfaces: water to air, and water to seafloor (both seafloor and air with less conductivity than seawater).…”
Section: Introductionmentioning
confidence: 99%